Social Studies Learning With Visualization, Auditory, Kinesthetic (VAK) Learning Model Assisted by Diorama Media Increases Student Knowledge Competence - Santhi, Ni Luh Komang Widya; Sri Asri, I Gusti Ayu Agung; Manuaba, Ida Bagus Surya (International Journal of Elementary Education, 2020)
The low studentsâ€™ competency of IPS (social science) is caused by the not optimal application of creative and innovative learning models and lack of learning media use. This research is aimed to analyze the impact of visualization, auditory, kinesthetic (VAK) learning model assisted with a diorama on social studies competency of elementary school students. It is quantitative research with the experimental design of quasi-experiment and non-equivalent pretest-posttest control group design. The population in this research are 275 grade IV students. Samples were taken with a random sampling technique, resulted in two classes. Class IV numbering 39 students were treated with VAK learning model assisted with diorama, and class IV numbering 37 students treated with conventional teaching and learning. Data were obtained by a common multiple-choice test and were then analyzed using polled variants t-test. It resulted the t count = 6,762 at 5% significance level with 39+37-2= 74 and t table = 1,993. Based on test criteria t count =6,726> t table =1,993. It leads to a conclusion that there is a significant influence of the VAK learning model aided with diorama media on IPS competency of grade IV students.Â